Faktor Penentu Ketepatan Waktu Pelaporan Keuangan pada Perusahaan Sektor Properti dan Real Estate - Mysia, Pipit; Masitoh W., Endang; Suhendro, Suhendro (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The goal of this observation is to ascertain how profitability, liquidity, leverage, company size, and company age affect how quickly financial reports are produced. This research was done on firms in the real estate and property sector that were listed on the Indonesia Stock Exchange between 2019 and 2021. Purposive sampling was used in the sampling process, which involved selecting 21 companies from a total of 63 research data and doing the sampling in accordance with predetermined standards. Descriptive analysis and logistic regression analysis make up the analytical model. The findings of this study suggest that profitability has an impact on how quickly real estate companies publish their financial data. In the property and real estate sector, liquidity, debt, firm age, and size have little impact on how quickly companies declare their financial results. Keywords: profitability, liquidity, leverage, company size, company age and timeliness